Otomasi Penerangan Ruangan Berbasis Arduino Uno - Muhammad Ricky; Habibullah Habibullah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Along with the advance of development, the need for electrical energy is increasing. Hence, all of that can be seen from the many uses of electronic devicesoand other mechanical devices in each building. As a result, every building requires an adequate supply of electricityoto beeableoto meet the needspof lighting or its mechanicalpproduction, therefore we should assist the state in using electrical energy wisely, namely by usinggit when it isineeded and notousing itowhen it is not needed, such as using room lighting when it is needed. This is small thing that is often underestimated by the community but haspa huge impact on wasting Electrical Energy, based on these problems, we created an automatic lighting system withothe aimpof beingoable tophelp use when needed, this tool was made using Arduino Uno as an automation center, and sensors PIR (Passive Infra Red) as a detector of the presence of room users, so that when a room user iskdetected by a PIR (Passive Infra Red) sensor, the lights in the room will turn on automatically and after five minutes ifothe sensorldoes notjdetect the presence of theiuser, room lights willoturn off automatically, so we hope this tool can help the community in energy saving efforts.